Pharmacy information systems in Tehran university hospitals and their relationship with pharmaceutical companies - Asadi, Farkhondeh; Moghaddasi, Hamid; Hosseini, Azamossadat; Sajjadi, Samad; Maserat, Elham (Archives of Advances in Biosciences, 2011)
<!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE AR-SA MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–> A pharmacy information system must retrieve process and update the information it obtains for safe and effective use of drugs. It is used to manage drug usage in the patient health care process and to communicate a large volume of information to pharmacy and pharmaceutical firms. Bearing in mind such issues, the current study adopted a descriptive method of research to investigate the pharmacy information systems in university hospitals and their relationship with pharmaceutical firms. The research data were collected through observation and interview based on a checklist and a questionnaire. Validity and reliability of the data gathering tools were specified through content validity and test re-test methods. The collected data were then analyzed, using a set of descriptive statistics. According to the results, pharmacy information systems in the hospitals under study were partially computerized. Databases for drugs, patients and prescriber databases, with different values of 50.1%, 21.9%, and 33.3% respectively, were not complete, as had been recorded in the pharmacy information system of the hospitals. The pharmacy information system is normally used to support therapeutic activities and the inventory, but such support had not been provided for 43.9 % of the hospitals. 32.2 % of the hospitals under study had not reported pharmaceutical information such as statistical data and drugs’ prices. Also, 27.3% of the pharmaceutical firms did not have any relationship with pharmacy information systems. Pharmaceutical companies had developed some relationship, on marketing issues, with hospital pharmacies. The findings were in favor of further therapeutic activities by pharmacy information systems, which could be achieved by improving relationship between hospitals and pharmaceutical firms, particularly in Tehran. This could help to manage drug consumption and supervision, after marketing, in order to eliminate adverse drug reactions and develop high quality pharmaceutical services.